Dinamika Hukum Perjanjian Elektronik: Tantangan Dan Prospek Dalam Era Digital - Togar Polmanto Winfernando; Ulil Amri Insan Kamil (JOURNAL SAINS STUDENT RESEARCH, 2023)
The digital era that continues to grow rapidly makes people's life patterns in making transactions also change. Electronic legal agreement is an engagement made by parties using mutual exchange of information through electronic media connected to the internet. This study aims to analyze the legal challenges of electronic agreements, related to legal challenges that arise in the practice of electronic agreements, including aspects of validity, electronic evidence, and consumer protection. The results showed that challenges in the form of requirements for electronic evidence to be valid in court have been explained in general in Article 6 of the ITE Law, but technically there are no rules to regulate them and the need for regulations on data security in electronic agreements. Therefore, the future prospect in the digital era with regard to electronic legal agreements is the need for regulatory revisions to increase legal clarity and certainty regarding the validity of electronic agreements.